Influência da taxa de dose da radiação beta na Allium cepa - Santos, Erison Fonseca dos (2022)
In general, the estimation of radiation dose in occupationally exposed individuals is done with physical methods. Among the biological methods to measure the radiation dose to which an individual has been exposed, there is cytogenetics. The frequency of chromosomal aberrations is related to the estimated absorbed dose and can be performed both in vitro and in vivo. Studies with direct measurements in humans are unfeasible and the use of animals is also quite complicated. In the search for materials from non-human biota that provide information on the effects of radiation on the environment and on humans, the onion (Allium cepa) appears. Allium cepa was chosen in this work because it is the gold standard plant for the determination of potential genotoxic chemical agents. This work consisted of irradiating onion (Allium cepa) roots with β particles from 90Sr/90Y sources at three different dose rates (7.2 mGy.s-1, 13.8 mGy.s-1, 19.5 mGy.s-1) and absorbed doses of 0.72, 2, and 4 Gy. All three sources induced cell damage with any of the doses used, with the appearance of micronuclei (MN) in greater numbers than in non irradiated cells. Different dose rates induced different behaviors in MN frequency as a function of absorbed dose. Samples that showed an unexpected behavior, with a decrease in the frequency of MN with increasing dose, had changes in the Mitotic Index(MI). It is concluded that to use the behavior of the MN frequency in Allium cepa cells in the assessment of absorbed dose, it is essential to also analyze the MI to verify if there was no cell death that will change the behavior generating false assessments. The increase in the frequency of radiation-induced MN together with the MI analysis gives evidence that Allium cepa can be used to demonstrate the effects caused by different dose rates of beta radiation, which may contribute to the understanding of biological effects induced by different dose rates, such as what happens during the use of flash radiotherapy.